Dampak Ketergantungan Konten Flexing pada Fase Quarter Life Crisis Mahasiswa Tingkat Akhir - Maghfira, Rifa; Rozaq, Miftahul (Fakultas Ilmu Komunikasi UKWMS, 2024)
Final-year students aged 20 years and over often feel various pressures to achieve a certain level of success or achievement. One of them is the pressure from flexing content that is often presented on social media. Dependence on flexing content can trigger anxiety about the future, which ultimately leads to the emergence of the quarter-life crisis phase. Through its content, social media indirectly influences students, especially in forming a crisis of self-confidence. This research aims to determine the influence of dependency on flexing content on the quarter-life crisis phase of final-year students and to find out how big the influence of dependency on flexing content is on the quarter-life crisis phase of final-year students. The media dependency theory introduced by Rokeach & Defleur (1976) is utilized as the primary foundation for this research. This research uses a quantitative approach with a survey method for 214 Communication Science students class of 2020 at Telkom University, Bandung. The results of this research obtained a significance value of 0.000 <0.05. The research findings indicate that the dependency on flexing content on social media has a considerable potential to induce anxiety about life direction, leading to the formation of the quarter-life crisis phase. This shows that the dependence on flexing content which includes cognitive, affective, and behavioral aspects influences the quarter-life crisis phase which includes hopes and dreams, educational challenges, religion and spirituality, work life, home, lovers, family, and friends, and identity in final-year students. final Communication Science class of 2020, Telkom University Bandung, with an influence level of 40.7%, and the other 59.3% were influenced by other factors not included in the research. Research implications and suggestions are also discussed.ABSTRAK Mahasiswa tingkat akhir yang berusia 20 tahun keatas seringkali merasakan berbagai tekanan untuk mencapai tingkat kesuksesan atau pencapaian tertentu. Salah satunya adalah tekanan dari konten flexing yang sering dihadirkan pada media sosial. Ketergantungan pada konten flexing dapat memicu kecemasan akan masa depan, yang akhirnya berujung pada munculnya fase quarter life crisis. Melalui kontennya, media sosial secara tidak langsung memberikan pengaruh terhadap mahasiswa, terutama dalam pembentukan krisis kepercayaan diri. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh ketergantungan konten flexing terhadap fase quarter life crisis mahasiswa tingkat akhir dan mengetahui seberapa besar pengaruh ketergantungan konten flexing terhadap fase quarter life crisis mahasiswa tingkat akhir. Teori ketergantungan media yang diperkenalkan Rokeach & Defleur (1976) digunakan sebagai landasan utama penelitian ini. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei kepada 214 mahasiswa Ilmu Komunikasi angkatan 2020 Universitas Telkom Bandung. Hasil penelitian ini memperoleh nilai signifikansi sebesar 0,000 < 0,05. Penelitian ini memperoleh temuan ketergantungan konten flexing di media sosial memiliki potensi cukup tinggi sebagai terjadinya kecemasan tentang arah hidup yang mengarah pada pembentukan fase quarter life crisis. Ini menunjukan bahwa ketergantungan konten flexing yang meliputi aspek kognitif, afektif dan perilaku berpengaruh terhadap fase quarter life crisis yang meliputi hopes and dream, education challenges, religion and spirituality, work life, home, lovers, family, and friends, dan identity pada mahasiswa tingkat akhir Ilmu Komunikasi angkatan 2020 Universitas Telkom Bandung, dengan tingkat pengaruh sebesar 40,7% dan 59,3% lainnya dipengaruhi oleh faktor lain yang tidak terdapat dalam penelitian. Implikasi dan saran penelitian juga dibahas.